Monte Carlo investigation of ferroelectric properties in thin films - Laosiritaworn Y. (2017)
In this work, the ferroelectric hysteresis in thin films was investigated with Monte Carlo simulation using the DIFFOUR Hamiltonian and the Metropolis algorithm. The field frequency, the filed amplitude and the thickness dependence of hysteresis properties were found. For instance, at high enough field, the area increases, maintains and reduces with increasing frequency. However, with increasing the film's thickness, the area increases over the whole considered frequencies, and the frequency at maximum area shifts to a lower frequency due to the stronger ferroelectric coupling in thicker films. In addition, the scaling relation among the hysteresis properties, the film's thickness and the field parameters in the power law form were also investigated, where the scaling exponents were compared and discussed with experiments on thin ferroelectric films. © (2010) Trans Tech Publications.